A Convenient Strategy for the Voltammetric Direct Determination of Ce(III) in Environmental Waters Using a Multi-Walled Carbon Nanotubes Modified Screen-Printed Carbon Electrode - Malgorzata Grabarczyk; Marzena Fialek; Edyta Wlazlowska (Molecules, 2024)
A simple and fast stripping voltammetric procedure for trace determination of Ce(III) in environmental water samples has been developed. The procedure of cerium determination in the presence of Alizarin S and acetate buffer was employed as the initial method. The adsorption material, multi-walled carbon nanotubes, was used as a screen-printed electrode modifier ensuring efficient accumulation of the Ce(III)-Alizarin S complex. The calibration graph for Ce(III) for an accumulation time of 60 s was linear in the range from 1 × 10−8 to 7 × 10−7 mol L−1 with the linear correlation coefficient r = 0.997. The detection limit was estimated from three times the standard deviation of low Ce(III) concentration and an accumulation time of 60 s was about 3.5 × 10−9 mol L−1. The proposed method was successfully applied to Ce(III) determination at trace levels in environmental water samples, such as river, lake and rain water with recoveries ranged from 93% to 98%.